Effects of Gossypetin from Hibiscus sabdariffa on Interleukin-6 Production in Porphyromonas gingivalis Lipopolysaccharide-Stimulated Human Gingival Fibroblasts - Ke Huang; Ki-Rim Kim (The Korean Society of Dental Hygiene Science, 2023)
Background: Periodontal disease is a major cause of tooth loss in adults and is a representative oral disease commonly suffered by most people around the world. Mainly the proliferation of Gram-negative bacteria and secreted virulence factors cause an inflammatory response and destroy periodontal tissue. Gossypetin, isolated from Hibiscus sabdariffa L, is known to have various pharmacological effects, including antibacterial and anticancer activities. We aimed to confirm the anti-inflammatory effect of gossypetin through interleukin-6 (IL-6) regulation in human gingival fibroblasts (HGFs) stimulated with lipopolysaccharide (LPS) of Porphyromonas gingivalis, a major cause of adult periodontitis.Methods: CCK-8 assay was performed to confirm the concentration-dependent cytotoxicity of gossypetin against HGFs. The secretion level and mRNA expression of IL-6, an inflammation-related cytokine, and the effect of gossypetin on these in HGFs stimulated with P. gingivalis LPS were confirmed by ELISA and qRT-PCR analysis, respectively. Results: Up to a concentration of 100 μM gossypetin with or without P. gingivalis LPS, the survival rate for HGFs was maintained at over 95% and showed no toxicity. ELISA and qRT-PCR analysis results showed that P. gingivalis LPS increased IL-6 secretion and mRNA levels in HGFs compared to the control group. However, this increase in IL-6 was significantly down-regulated by gossypetin treatment in a dose-dependent manner. In particular, 80 μM gossypetin inhibited IL-6 production to the level of the control group. Conclusion: These results indicated that gossypetin attenuated IL-6 production in HGFs stimulated by P. gingivalis LPS, which may ultimately suppress the inflammatory response in periodontal tissue. Therefore, gossypetin may have potential as a natural ingredient for the prevention and treatment of periodontal disease.